Industrial Organizations Adapting to the Novel EU Taxonomy While Developing Socio-Technical Systems: A Literature Review - Henri Giudici; Fabio Bento; Kristin Falk (Systems)
The EU taxonomy defines criteria for economic activities committed to a net zero emission by 2050, and other environmental goals. Its overall goal is to direct investments to economic activities aligned with the European Green Deal and, thereby, classified as sustainable. For industrial organizations, there is an urgent need to develop adaptive capabilities to meet the requirements set by the new taxonomy. The present scoping review contributes by analyzing academic publications on this topic through the lens of a complex science and systems approach. It analyzes academic publications on the EU taxonomy, related to industrial organizations and their development of socio-technical systems. At the initial stage, 526 scientific publications were retrieved from three web repositories (Scopus, World of Science, and Scholar). Only eight publications matched the selection criteria and constitute the data of this study. Results indicate that there is a lack of holistic perspectives and an unbalanced system response to the EU taxonomy. Adopting a systems approach can help industrial organizations navigate the intricate dynamics of a sustainable transition, striking a balance between adhering to the EU taxonomy and maintaining market competitiveness. The findings emphasize the importance of trans-disciplinary approaches and the need for agile and adaptive ways of learning inside industrial organizations.